Psalms - Vivaldi, Antonio and Szekeres, Ferenc and Takács, Klára and Bársony, László and Bartha, Zsolt and Bartányi, István and Áchim, Erzsébet (Hungaroton, 1985)
Enth.&&Nisi Dominus, psalm 126, RV 608$rPsalmen R 608
https://katalog.adlr.link/Record/0-1600445764